Depression and anxiety mediate the relationship between COVID-19 stay-at-home orders and tobacco and marijuana use - Geoffrey Carney-Knisely; Jolynn Pek; Amy K. Ferketich; Tasleem J. Padamsee; Tamar Gur; Parvati Singh (PLoS ONE, 2025)
Background The COVID-19 pandemic had notable impacts on the mental health of the U.S. population. There were concerns about how the pandemic affected substance use in the population. The overall objective of this study was to assess whether COVID-19 Stay-At-Home (SAH) orders, an ambient ecological stressor, as well as the severity of depressive and anxious symptoms, can explain tobacco and marijuana use. Methods Data come from the first seven waves of the Understanding America Study, a nationally representative longitudinal web-based panel study. A total of 7,554 persons participated in the first seven waves, resulting in 43,582 observations. Cigarette use as a measure was not included until wave four of the study; 7,034 persons participated in waves four through seven, resulting in 24,893 observations. The primary outcomes were self-reported past seven-day use of cigarette products and past seven-day use of marijuana products. Self-reported depressive and anxious symptom severity, the proposed mediator, was measured using the Patient Health Questionnaire-4 (PHQ-4). The primary exposure was a binary indicator for the presence of an SAH order. All variables were measured biweekly. Generalized Estimating Equations (GEE) were used to assess single-mediator models. Results Persons under SAH orders had 2.18 (95% CI: 1.27, 3.73) times the odds of moderate-to-severe depression across the first seven waves, relative to those living in states without SAH orders. Those with moderate-to-severe depression and anxiety had lower odds of both marijuana (OR = 0.37, 95% CI: 0.17, 0.84) and cigarette use (OR = 0.29, 95% CI: 0.13, 0.65) compared to those with normal-mild PHQ-4 scores. Worsened mental health within a person resulted in 0.22 (95% CI: 0.12, 0.40) times the odds of marijuana use and 0.26 (95% CI: 0.15, 0.47) times the odds of cigarette use. Tests of the joint effects suggest evidence of multiple mediated pathways.